PENERAPAN MODEL PASPOR (PAIRING,SQUARE,PRESENTATION,REPETITION) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VII SMPN 02 KEPENUHAN HULU - Yuriska Riska; Jufri Jufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ problem-solving ability in algorithm material in Informatics learning, as indicated by students’ difficulties in organizing logical and systematic solution steps and the teacher-centered learning process. This study aims to determine the differences in students’ problem-solving abilities before and after the implementation of the PASPOR (Pairing, Square, Presentation, Repetition) learning model, as well as to analyze its effect and effectiveness. This research employed a quantitative approach with an experimental design involving seventh-grade students of SMP Negeri 02 Kepenuhan Hulu in the 2025/2026 academic year. Data were collected through tests, questionnaires, observations, and documentation, and were analyzed using descriptive quantitative analysis by comparing pretest and posttest results and calculating the N-Gain score. The results showed that the implementation of the PASPOR learning model was able to improve students’ problem-solving abilities in algorithm material. This improvement occurred as students were actively involved in learning through pairing activities, group discussions, presentations, and repetition, which enhanced their conceptual understanding in a more systematic manner. Therefore, the PASPOR model can be considered an effective alternative learning model to improve students’ problem-solving abilities in Informatics learning. Keywords: PASPOR learning model, algorithms, problem-solving ability, informatics learning, cooperative learning